1996
DOI: 10.1002/(sici)1096-8628(19960809)64:2<246::aid-ajmg2>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term potentiation in the hippocampus of fragile X knockout mice

Abstract: To gain more insight in the physiological function of the fragile X gene (FMR1) and the mechanisms leading to fragile X syndrome, the Fmr1 gene has been inactivated in mice by gene targeting techniques. In the Morris water maze test, the Fmr1 knockout mice learn to find the hidden platform nearly as well as the control animals, but show impaired performance after the position of the platform has been modified. As malperformance in the Morris water maze test has been associated with impaired long-term potentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 0 publications
7
61
0
Order By: Relevance
“…Although it is consistently reported that LTD is exaggerated in hippocampus (Huber et al, 2002;Zhang et al, 2009) and cerebellum (Koekkoek et al, 2005), LTP impairment depends on the region of the brain as well as the induction protocols. Some reports find that LTP is not affected in the hippocampus (Bear et al, 2004;Godfraind et al, 1996;Paradee et al, 1999;Zhang et al, 2009), whereas others show that LTP is reduced in the hippocampus (Hu et al, 2008;Larson et al, 2005;Lauterborn et al, 2007;Lee et al, 2011;Shang et al, 2009). In the ACC, we reported that the early phase of LTP was impaired in cingulate pyramidal cells (Zhao et al, 2005a).…”
Section: Fmr1 Ko Mice Exhibited Reduced L-ltp In the Accmentioning
confidence: 63%
See 1 more Smart Citation
“…Although it is consistently reported that LTD is exaggerated in hippocampus (Huber et al, 2002;Zhang et al, 2009) and cerebellum (Koekkoek et al, 2005), LTP impairment depends on the region of the brain as well as the induction protocols. Some reports find that LTP is not affected in the hippocampus (Bear et al, 2004;Godfraind et al, 1996;Paradee et al, 1999;Zhang et al, 2009), whereas others show that LTP is reduced in the hippocampus (Hu et al, 2008;Larson et al, 2005;Lauterborn et al, 2007;Lee et al, 2011;Shang et al, 2009). In the ACC, we reported that the early phase of LTP was impaired in cingulate pyramidal cells (Zhao et al, 2005a).…”
Section: Fmr1 Ko Mice Exhibited Reduced L-ltp In the Accmentioning
confidence: 63%
“…To date, most LTP studies have been focusing on the hippocampus of Fmr1 KO mice. In the hippocampus, some studies show that LTP is intact (Auerbach and Bear, 2010;Bear et al, 2004;Godfraind et al, 1996;Paradee et al, 1999), whereas others confirm the deficit of LTP by using different LTP induction protocols (Hu et al, 2008;Lauterborn et al, 2007;Lee et al, 2011;Shang et al, 2009). Furthermore, L-LTP of the hippocampus was found to be normal in Fmr1 KO mice (Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Initial electrophysiological studies examining the NMDA receptor-dependent LTP in the hippocampus did not find a difference in early-or late-phase LTP between wild-type and Fmr1 knockout mice (Godfraind et al, 1996;Paradee et al, 1999). Interestingly, it was Figure 3.…”
Section: The Mouse Model and Molecular Mechanisms Of Fragile X Syndromementioning
confidence: 97%
“…There are two wellstudied forms of LTD, N-methyl-D-aspartate receptormediated LTD (NMDAR-LTD) and mGluR-LTD [54]. Although LTP is unaffected in the hippocampus of Fmr1-knockout mice, mGluR-LTD, but not NMDAR-LTD, is significantly altered [53,55]. Using two distinct induction protocols (synaptic stimulation and induction by the highly specific group 1 mGluR agonist DHPG), it was found that mGluR-LTD is significantly increased in the hippocampus of Fmr1-knockout mice.…”
Section: How Does Fmrp Perform This Role?mentioning
confidence: 99%